Electrosynthetic C−O Bond Activation in Alcohols and Alcohol Derivatives. (5th December 2022) - Villo, Piret; Shatskiy, Andrey; Kärkäs, Markus D.; Lundberg, Helena
Abstract: Alcohols and their derivatives are ubiquitous and versatile motifs in organic synthesis. Deoxygenative transformations of these compounds are often challenging due to the thermodynamic penalty associated with the cleavage of the C−O bond. However, electrochemically driven redox events have been shown to facilitate the C−O bond cleavage in alcohols and their derivatives either through direct electron transfer or through the use of electron transfer mediators and electroactive catalysts. Herein, a comprehensive overview of preparative electrochemically mediated protocols for C−O bond activation and functionalization is detailed, including direct and indirect electrosynthetic methods, as well as photoelectrochemical strategies. Abstract : Deoxygenative transformations of alcohols and their derivatives are often challenging due to the thermodynamic penalty associated with the cleavage of the C−O bond. This Review includes preparative protocols and their mechanistic aspects for the activation and functionalization of C−O bonds, detailing direct and indirect electrosynthetic methods, as well as photoelectrochemical strategies.